Environmental knowledge and behavioural outcomes of tourism students in Australia: towards testing a range of mediation and moderated mediation effects - Fatima, J.; Khan, H.; Goh, E. (Routledge, 2014)
Our study examines the environmental knowledge (EK) and behavioural outcomes of students studying ecotourism in Sydney, Australia. Three competing models were tested to examine the relationships between EK, participation intention (PI) in ecotourism programs, landscape likeability (LL) and social interactions (SI); and the study also tested the moderated mediation influence of gender differences and relationship length on mediators. Partial least squares-based structural equation modelling (PLS-SEM) was used to analyse the data collected from 173 residential tourism students. Key findings suggest whilst LL and PI are significant outcomes of EK, LL has a stronger mediating effect on PI compared to SI; and all mediation effects are further moderated by gender differences. However, only Model 3 confirms the moderating effect of the length of relationship. Noting the key role that EK plays in influencing their PI and LL, our study also suggests ways of developing the tourism students’ EK, through various experiential and pedagogical interventions.